2018
DOI: 10.4314/ahs.v18i3.18
|View full text |Cite
|
Sign up to set email alerts
|

The association between periodontal disease and adverse pregnancy outcomes in Northern Tanzania: a cross-sectional study

Abstract: Background: For the past two decades, studies have investigated the relationship between periodontal disease and adverse pregnancy outcomes such as pre-eclampsia, preterm birth, low birth weight and preterm premature rupture of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 40 publications
1
40
1
23
Order By: Relevance
“…Women with high-titer active syphilis were at the greatest risk of having PTB (ARR 6.1 (2.5-15.3) [49]. Presence of periodontal disease (AOR 2.32; 95%CI: 1.33-4.27) [34] and periodontitis (at least three sites from different teeth with clinical attachment loss greater than or equal to4 mm [85] was significantly associated with PTB. Maternal depression increased the probability of having PTB (ARR 4.13; 95% CI: 2.82-17.42) [65].…”
Section: Medical Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Women with high-titer active syphilis were at the greatest risk of having PTB (ARR 6.1 (2.5-15.3) [49]. Presence of periodontal disease (AOR 2.32; 95%CI: 1.33-4.27) [34] and periodontitis (at least three sites from different teeth with clinical attachment loss greater than or equal to4 mm [85] was significantly associated with PTB. Maternal depression increased the probability of having PTB (ARR 4.13; 95% CI: 2.82-17.42) [65].…”
Section: Medical Conditionsmentioning
confidence: 97%
“…The studies were included from 11 East African countries. Nineteen studies were from Tanzania [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The prevalence of periodontal disease among pregnant women varies in different populations [11][12][13]. Moreover, several factors such as age, parity, lower level of education and anaemia were identified as risk factors for periodontal disease during pregnancy [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…The association between CP and LBW was rst reported by Offenbacher et al [1]. Many epidemiological studies have reported that pregnant women with CP are several times more likely than women without CP to have a preterm LBW infant [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Additionally, some studies have found that treatment for periodontitis is effective for preventing LBW [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic bacterium of CP and chemical mediators produced by in ammation in gingiva were considered to penetrate into weak capillary blood vessels, and then to cord blood through the placenta [2][3][4]. Some researchers have reported that CP in uences the development of LBW [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], whereas others have denied such an association [23][24][25][26][27]. Therefore, no consensus has been reached on the association between CP and LBW [28][29][30][31], and more studies are needed to address this issue.…”
Section: Introductionmentioning
confidence: 99%